Tadpole of Leptodactylus oreomantis Carvalho, Leite & Pezzuti 2013 (Anura, Leptodactylidae) - Mercês, Ednei De Almeida; Magalhães, Felipe De Medeiros; Amado, Talita Ferreira; Juncá, Flora Acuña; Garda, Adrian Antonio (Zootaxa, 2015)
Leptodactylus oreomantis, a member of Leptodactylus fuscus species group (sensu Heyer 1978), is a leptodactylid frog endemic to the montane rocky fields of Chapada Diamantina (the northern portion of the Espinhaço mountain range), Bahia State, Brazil (Carvalho et al. 2013). Although tadpole morphology provides relevant information for anuran taxonomy and systematics (see Langone & de Sá 2005; Miranda et al. 2014), only calls and adult morphology were evaluated in the description of this species. Herein, we describe and illustrate the external morphology and internal oral anatomy of L. oreomantis tadpoles and compare it with tadpoles of related species.